2015
DOI: 10.1517/14712598.2015.1036736
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic application of CRISPR/Cas9 technologies for HIV

Abstract: Introduction The use of antiretroviral therapy (ART) has led to a significant decrease in morbidity and mortality in HIV-infected individuals. Nevertheless gene-based therapies represent a promising therapeutic paradigm for HIV-1, as they have the potential for sustained viral inhibition and reduced treatment interventions. One new method amendable to a gene-based therapy is the clustered regularly interspaced palindromic repeats (CRISPR)/Cas9 gene editing system. Areas covered CRISPR/Cas9 can be engineered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 80 publications
0
62
0
3
Order By: Relevance
“…Specifically, it has recently been shown that the use of virus specific gRNAs can result in the mutational inactivation of viral genomes of viruses such as HPV, HBV, HSV, EBV and HIV-1, mostly by targeting the integrated viral genomes or viral DNA in latently infected cells2122232425262728293031323436373839. Here we show that it is also possible to use the CRISPR/Cas9 system to inhibit acute virus infection.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Specifically, it has recently been shown that the use of virus specific gRNAs can result in the mutational inactivation of viral genomes of viruses such as HPV, HBV, HSV, EBV and HIV-1, mostly by targeting the integrated viral genomes or viral DNA in latently infected cells2122232425262728293031323436373839. Here we show that it is also possible to use the CRISPR/Cas9 system to inhibit acute virus infection.…”
Section: Discussionmentioning
confidence: 66%
“…The Cas9 endonuclease together with a small guide RNA (gRNA) can introduce double strand breaks in targeted DNA in a sequence-specific manner20. Similar to the original function of CRISPR, a microbial nuclease system serving as a defense mechanism against invading phages and plasmids, CRISPR/Cas9 has now been employed to specifically target mammalian viral genomes, including those of human papillomaviruses (HPV), Hepatitis B virus (HBV), Epstein-Barr virus (EBV) and HIV-1 (Reviewed in refs 21 and 22). In these cases, the CRISPR/Cas9 system introduced double strand breaks in the viral DNA genome associated with mutational inactivation of viral genes resulting in the inhibition of viral protein production and viral DNA replication.…”
mentioning
confidence: 99%
“…The technique can be used in biomedicine to develop tissue-based treatments for cancer and other diseases [27]. For example, CRISPR/ Cas9 may target HIV provirus to mediate excision of the integrated viral genome or prevent cellular entry of the virus [28]. The technique has also shown that can correct the mutation causing cystic fibrosis in intestinal stem cells derived from patients [29].…”
Section: Applications Of the Crispr/cas9 Systemmentioning
confidence: 99%
“…It would permit to understand the underpinnings behinds of alterations of cellular homeostasis when a cell is infected (Moore, 2000). Additionally, analysis of integration process is important in HIV-induced disease, in Lentivirus-based gene therapy and new therapeutic options actually developed (Saayman, et al, 2015;Cereseto y Giacca, 2004).…”
Section: Introductionmentioning
confidence: 99%